Retrosternal goiter masquerading as type II respiratory failure. A case report. (May 2022) - Bakkar, Sohail; Hamdeh, Queen; Haddadin, Robert; Donatini, Gianluca; Papavramidis, Theodosios S.; Tawalbeh, Mohamed
Abstract: Introduction and importance: Retrosternal Goiter (RG) represents a challenging clinical entity for surgeons. Although the vast majority of cases are successfully operated via a cervical access, there still remains a small minority that require an extra-cervical approach, even in experienced hands. Factors that shift the odds towards an extra-cervical approach are mainly related to the anatomic characteristics of the retrosternal mass. Case presentation: We herein report a case of RG presenting as type 2 respiratory failure without a palpable neck mass, in an 81-year-old female. Despite her history of subtotal thyroidectomy for Graves' disease, the patient's chest x-ray showed a central mediastinal mass shifting the trachea to the left. The retrosternal mass extended below the aortic arch, and carina on computed tomography. It also extended into the posterior mediastinum. All these anatomical features of the RG along with the patient's previous neck surgery were in favor of an extra-cervical approach. Nevertheless, a cervical approach was attempted, and was concluded successfully. Conclusion: CT plays a key role in determining the likelihood of requiring an extra-cervical approach in RG. Even if the odds seem to be in favor of an extra-cervical approach, an attempt to remove the goiter through a cervical incision should always be made by an experienced surgeon, using all available techniques, and taking all required precautions, on account of less risk of surgical and aesthetic damage obtained with this approach. Highlights: Respiratory failure is an unprecedented manifestation of retrosternal goiter (RG). CT plays an important role in determining the likelihood of requiring an extra-cervical approach for RG. An ectopic goiter, previous neck surgery, extension below the level of the carina and/or into the posterior mediastinum favor an extra-cervical approach. A cautious attempt to remove RG through a cervicotomy should always be made, on account of reduced risk of surgical and aesthetic harm with this approach. If RG is performed by a skilled surgeon, familiar with its unique pitfalls, the assistance of a thoracic surgeon may seldom be required.